2019
DOI: 10.1101/609016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genetic architecture of Parkinson disease in Spain: characterizing population-specific risk, differential haplotype structures, and providing etiologic insight

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Analyzing large case-control cohorts has paved the way for the discovery of genetic risk variants for PD (12). Nevertheless, heterogeneity across cohorts from different countries or even regions within countries may mask genetic associations specific to sub-populations (22, 23). We investigated environmental factors and the genetic architecture of PD in a PD case-control cohort selectively recruited from the southernmost region of Sweden.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Analyzing large case-control cohorts has paved the way for the discovery of genetic risk variants for PD (12). Nevertheless, heterogeneity across cohorts from different countries or even regions within countries may mask genetic associations specific to sub-populations (22, 23). We investigated environmental factors and the genetic architecture of PD in a PD case-control cohort selectively recruited from the southernmost region of Sweden.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying regions of extended homozygosity can help identify rare recessive risk variants contributing to disease, and increased level of genomic homozygosity has been observed in PD patients with an early PD diagnosis compared to controls (48). It has also been observed that PD patients exhibit overall excess homozygosity in genes/loci previously associated with PD (22). We therefore investigated ROH in the entire study cohort as well as in a subset of PD patients with an early PD diagnosis (AAD < 50 years) and/or with a first-degree relative with PD (N=147).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations